SRATEGI KEPALA SEKOLAH DI DAERAH PEDESAAAN UNTUK MENINGKATKAN MUTU PENDIDIKAN DAN KARAKTER WARGA SEKOLAHNYA - Liskayani, Liskayani; Sulastri, Sulastri (Graduate Program Magister Manajemen Pendidikan, 2018)
This study aimed at determining what strategies are used by the headmaster who served in rural areas with various challenges faced to improve the quality of education and character of the citizens of the school in accordance with the goals of national education. This research was a qualitative research, where in this paper researchers see the steps and efforts made by the headmaster while facing an event that is happening. Data collection technique in this study was interview to the principal of SD Negeri 17 Air Kumbang. From the results of the research, it can be seen that the strategy done by the headmaster of SD Negeri 17 Air Kumbang to improve the quality of education and character of the students is settle in the location where he served, socialize the surrounding community about the importance of education in school-aged children, improve the qualification of teachers, improving the competence of students and graduates, improving the character of students and teachers through extracurricular activities scouting and completing facilities and infrastructure in schools.